2019
DOI: 10.1016/j.stemcr.2019.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Pluripotent Stem Cell-Derived Cerebral Organoids Reveal Human Oligodendrogenesis with Dorsal and Ventral Origins

Abstract: The process of oligodendrogenesis has been relatively well delineated in the rodent brain. However, it remains unknown whether analogous developmental processes are manifested in the human brain. Here we report oligodendrogenesis in forebrain organoids, generated by using OLIG2-GFP knockin human pluripotent stem cell (hPSC) reporter lines. OLIG2/GFP exhibits distinct temporal expression patterns in ventral forebrain organoids (VFOs) versus dorsal forebrain organoids (DFOs). Interestingly, oligodendrogenesis ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
90
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(104 citation statements)
references
References 68 publications
3
90
0
Order By: Relevance
“…To induce neural differentiation, we used three hPSC lines, including two healthy individual-derived human induced pluripotent stem cells (hiPSCs) and one human embryonic stem cell (hESC), with dual inhibition of SMAD signaling (Chambers et al, 2009). At day 7, we plated the embryoid bodies (EB) on dishes, and on day 14, we manually separated neural rosettes from surrounding cells and further expanded as pNPCs, as described in our previous studies (Chen et al, 2016;Xu et al, 2019). The identity of hPSCs-derived pNPCs was confirmed by staining with Nestin, a marker for NPCs (Wiese et al, 2004) ( Figure 1B).…”
Section: Generation Of Brain Organoid With a Controllable Microglialmentioning
confidence: 99%
See 2 more Smart Citations
“…To induce neural differentiation, we used three hPSC lines, including two healthy individual-derived human induced pluripotent stem cells (hiPSCs) and one human embryonic stem cell (hESC), with dual inhibition of SMAD signaling (Chambers et al, 2009). At day 7, we plated the embryoid bodies (EB) on dishes, and on day 14, we manually separated neural rosettes from surrounding cells and further expanded as pNPCs, as described in our previous studies (Chen et al, 2016;Xu et al, 2019). The identity of hPSCs-derived pNPCs was confirmed by staining with Nestin, a marker for NPCs (Wiese et al, 2004) ( Figure 1B).…”
Section: Generation Of Brain Organoid With a Controllable Microglialmentioning
confidence: 99%
“…The hiPSC lines were generated from healthy adult-derived fibroblasts using the "Yamanaka" reprogramming factors in our previous study (Chen et al, 2014). The hPSC line has been fully characterized, including karyotyping, teratoma assay, Pluritest (www.PluriTest.org), DNA fingerprinting STR (short tandem repeat) analysis and gene expression profiling (Xu et al, 2019;Xu et al, 2020). The hPSCs, from passage number 15-30, were cultured on dishes coated with hESC-qualified Matrigel Human pNPCs were generated from hPSCs as previously reported (Chen et al, 2016;Xu et al, 2019).…”
Section: Generation Culture and Quality Control Of Hpsc Linesmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, self-patterning of organoids precursors can be restricted to forebrain fate by inhibiting TGF-β, BMP, and WNT pathways ( Figure 1A ; Eiraku et al, 2008 ; Kadoshima et al, 2013 ). By supplying additional patterning factors (such as WNT3A, SHH, insulin, and BMP7), forebrain fate can be further confined to produce organoids resembling any discrete part of the forebrain region, including cerebral cortex, optic cup, hippocampal, choroid plexus, subpallium, thalamus, and hypothalamus ( Wataya et al, 2008 ; Eiraku et al, 2011 ; Nakano et al, 2012 ; Germain et al, 2013 ; Kadoshima et al, 2013 ; Liu et al, 2013 ; Maroof et al, 2013 ; Nicholas et al, 2013 ; Mariani et al, 2015 ; Sakaguchi et al, 2015 ; Qian et al, 2016 ; Shiraishi et al, 2017 ; Kim et al, 2019b ; Xiang et al, 2020a ). Midbrain organoids are generated by combining TGF-β and BMP inhibition with WNT and SHH activation, and FGF8 treatment ( Jo et al, 2016 ; Kim et al, 2019a ), whereas cerebellum organoids are produced by timed and combinatory treatment with a series of patterning factors, including TGF-β and BMP inhibitors, insulin, FGF2, FGF19, and SDF1 ( Figure 1A ; Muguruma et al, 2015 ).…”
Section: Brain Organoids and Technologiesmentioning
confidence: 99%
“…To study oligodendrogenesis in vitro, Madhavan et al (2018) exposed cortical spheroids to known oligodendrocyte lineage growth factors and hormones to promote OPC proliferation and further maturation into myelinating oligodendrocytes that were capable of forming myelin sheaths wrapped around axons within the neurosphere. Kim et al (2019) also used a protocol to accelerate oligodendrocyte maturation and demonstrated differences in the timing of oligodendrogenesis and maturation when the protocol was applied to ventral versus dorsal patterned forebrain organoids. These differences mimicked in vivo observations in mice, where ventral neural precursors undergo a wave of oligodendrogenesis prior to the dorsal wave (Kessaris et al 2006).…”
Section: Other Neural Cell Typesmentioning
confidence: 99%